Oil and Gas Storage Facilities Construction Operations Standardization - Bondar, Victor; Bondar, Liudmyla; Petrash, Oleksandr; Popovych, Nataliia (International Journal of Engineering and Technology, 2018)
This is the first research that provides the calculation of time and labor standards for foundation works at oil and gas storage facilities construction. A foundation works performance for two identical vertical steel tanks is under investigation. The reinforced soil-cement piles are suggested as the most economical way of foundation works performance at gas and oil storage facilities The deep soil mixing technology is considered. The detailed description of suggested technology is presented along with time spent for each technological element. This paper provides data on the machinery and materials needed for construction. A time study method was applied to compile a working day photo-fixation. The obtained data were processed using the method suggested by engineer Prussak. The nonlinear correlation of drilling time versus depth of reinforced soil cement piles was obtained. The influence of geotechnical conditions on time and labor consumption is presented. Time and labor standards for manufacturing 1 m3 of soil-cement piles have been calculated.Â Â Â
Keywords: cement; clay; cost rates; drilling; deep soil mixing technology; geotechnical conditions; loess loam; labor; photo-fixation; reinforced soilcement pile; soil; time; vertical oil tank.